Magnetic tunnel junction and preparation method thereof

The magnetic tunneling junction of the Cr3Te4/WS2/Fe3GeTe2 layer structure is prepared by physical vapor deposition and dry transfer methods, which solves the problem of poor performance of the existing magnetic tunneling junction, and achieves the effect of low resistance and low power consumption, and is suitable for low-work functional magnetic memory.

CN119894355APending Publication Date: 2025-04-25CHANGSHA SEMICON TECH & APPL INNOVATION RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510062647.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the preparation process, existing magnetic tunneling junctions are prone to atomic diffusion, amorphous or polycrystalline structures, which affects performance, and are prone to poor magnetization characteristics outside the plane, resulting in increased power consumption.

Method used

The magnetic tunneling junction with the Cr3Te4/WS2/Fe3GeTe2 layer structure was prepared by physical vapor deposition and dry transfer methods. The thickness of the WS2 layer was controlled to be between 1.4-4.2nm, and the linear tunneling mode was realized, and the resistance was adjusted by adjusting the magnetization direction of Cr3Te4 and Fe3GeTe2.

Benefits of technology

Magnetic tunneling junction with low resistance and low power consumption is realized, the preparation process is simplified, the storage density and flip efficiency are improved, and it is suitable for low-work functional magnetic memory.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894355A_ABST
    Figure CN119894355A_ABST
Patent Text Reader

Abstract

The invention relates to a magnetic tunnel junction and a preparation method thereof. The magnetic tunnel junction comprises a Cr3Te4 layer, a WS2 layer and a Fe3GeTe2 layer which are stacked in sequence, wherein the thickness of the WS2 layer is less than or equal to 4.2 nm. The IV output curve of the magnetic tunnel junction is a straight line under the action of the voltage of 0-1V, and the magnetic tunnel junction has a smaller resistance area (RA) less than 400k omega.mu m < 2 > during working.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a magnetic tunnel junction and a preparation method thereof, in particular to a magnetic tunnel junction with low-resistance two-dimensional van der Waals contact and a preparation method thereof, belonging to the field of spin electronic devices. Background Art

[0002] Compared with other traditional non-volatile storage technologies, magnetic random access memory (MRAM) has faster read and write speeds, lower power consumption, and higher durability. Therefore, it has been rapidly developed in the field of modern electronic technology. [1,2] Magnetic tunnel junction (MTJ) is a data storage unit in magnetic random access memory. Its basic structure consists of two ferromagnetic layers sandwiched by a thin layer of insulating material or semiconductor material. [3,4] The working principle of the magnetic tunnel junction is based on the quantum tunneling phenomenon. Electrons can tunnel through the insulating layer, and the tunneling probability is affected by the electron spin, which directly affects the resistance of the magnetic tunnel junction. [5] When the magnetization directions of the two ferromagnetic layers change relative to each other, the resistance changes significantly, that is, when the magnetization directions of the two layers are parallel, the resistance is low, and when their magnetization directions are antiparallel, the resistance is high. [5] This unique relationship between resistance and magnetic structure arrangement enables the magnetic tunnel junction to be used as a digital signal in a von Neumann computer, thereby achieving further logical operations.

[0003] The traditional method of preparing magnetic tunnel junctions is to construct ferromagnetic layer / intermediate layer / ferromagnetic layer through magnetron sputtering or molecular beam epitaxy. However, problems such as atomic diffusion and amorphous or polycrystalline structure of the film may occur during the coating process, which will affect the performance of the magnetic tunnel junction. [6,7] When using the coating process to prepare magnetic tunnel junctions, the lattice matching problem needs to be considered, which increases the difficulty of preparing high-quality magnetic tunnel junctions. In addition, the ultra-thin magnetic film prepared by the coating process has a strong demagnetization energy in the direction perpendicular to the film plane, and the easy magnetization axis of the film is usually parallel to the plane of the film. [3,8] However, the out-of-plane magnetic tunnel junction is designed to be elliptical or rectangular, and the device area is relatively large, which will affect the storage density of the magnetic random access memory. At the same time, the in-plane easy magnetization magnon is relatively low in efficiency when flipping, resulting in relatively large flipping power consumption, so it is necessary to develop magnons with out-of-plane easy magnetization. [1,9,10] Although in some multilayer film structures, due to the structural asymmetry, strong magnetocrystalline anisotropy can be generated at the interface, making the easy magnetization axis perpendicular to the film surface, the magnetism of the film is very sensitive to thickness. A thickness difference of one nanometer will seriously affect the direction of the easy magnetization axis. [9] .

[0004] Due to their single crystal characteristics, two-dimensional magnetic nanosheets usually show an easy magnetization axis along a certain direction. At the same time, two-dimensional magnetic nanosheets are usually thinned along the c-axis direction of the crystal, and the easy magnetization axis is usually also in the c-axis direction, so most of the two-dimensional magnetic nanosheets show the characteristics of easy magnetization out of the plane. [11-16] The out-of-plane magnetic tunnel junction prepared by two-dimensional magnetic nanosheets is generally prepared by organic-assisted transfer. The thickness of the intermediate layer and some organic residues will cause the magnetic tunnel junction to have a large resistance when working, which seriously increases the power consumption. [17-19] .

[0005] References:

[0006] [1]S.Bhatti,R.Sbiaa,A.Hirohata,H.Ohno,S.Fukami,SNPiramanayagam,Mater.Today 2017,20,530.

[0007] [2] B. Dieny, IL Prejbeanu, K. Garello, P. Gambardella, P. Freitas, R. Lehndorff, W. Raberg, U. Ebels, SODemokritov, J. Akerman, A. Deac, P. Pirro, C. Adelmann, A. Anane, AVChumak, A. Hirohata, S. Mangin, SO Valenzuela, MC M.d'Aquino,G.Prenat,G.Finocchio,L.Lopez-Diaz,R.Chantrell,O.Chubykalo-Fesenko,P.Bortolotti,Nat.Electron.2020,3,446.

[0008] [3] A. Du, D. Zhu, K. Cao, Z. Zhang, Z. Guo, K. Shi, D. Xiong, R. Xiao, W. Cai, J. Yin, S. Lu, C. Zhang, Y. Zhang, S. Luo, A. Fert, W. Zhao, Nat. Electron. 2023, 6, 425.

[0009] [4]M.Wang,W.Cai,D.Zhu,Z.Wang,J.Kan,Z.Zhao,K.Cao,Z.Wang,Y.Zhang,T.Zhang,C.Park,J.-P.Wang,A.Fert,W.Zhao,Nat.Electron.2018,1,582.

[0010] [5]K.-H.Min,D.H.Lee,S.-J.Choi,I.-H.Lee,J.Seo,D.W.Kim,K.-T.Ko,K.Watanabe,T.Taniguchi,D.H.Ha,C.Kim,J.H.Shim,J.Eom,J.S.Kim,S.Jung,Nat.Mater.2022,21,1144.

[0011] [6]H.Wang,H.Wu,J.Zhang,Y.Liu,D.Chen,C.Pandey,J.Yin,D.Wei,N.Lei,S.Shi,H.Lu,P.Li,A.Fert,K.L.Wang,T.Nie,W.Zhao,Nat.Commun.2023,14,5173.

[0012] [7]N.Sato,F.Xue,R.M.White,C.Bi,S.X.Wang,Nat.Electron.2018,1,508.

[0013] [8]H.Wu,A.Chen,P.Zhang,H.He,J.Nance,C.Guo,J.Sasaki,T.Shirokura,P.N.Hai,B.Fang,S.A.Razavi,K.Wong,Y.Wen,Y.Ma,G.Yu,G.P.Carman,X.Han,X.Zhang,K.L.Wang,Nat.Commun.2021,12,6251.

[0014] [9]S.Ikeda,K.Miura,H.Yamamoto,K.Mizunuma,H.D.Gan,M.Endo,S.Kanai,J.Hayakawa,F.Matsukura,H.Ohno,Nat.Mater.2010,9,721.

[0015]

[10] IHKao, R.Muzzio, H.Zhang, M.Zhu, J.Gobbo, S.Yuan, D.Weber, R.Rao, J.Li, JHEdgar, JEGoldberger, J.Yan, DGMandrus, J.Hwang, R.Cheng, J.Katoch, S.Singh, Nat.Mater.2022, 21, 1029.

[0016]

[11] B. Li, X. Deng, W. Shu, X. Cheng, Q. Qian, Z. Wan, B. Zhao, X. Shen, R. Wu, S. Shi, H. Zhang, Z. Zhang, X. Yang, J. Zhang, M. Zhong, Q. Xia, J. Li, Y. Liu, L. Liao, Y. Ye, L. Dai, Y. Peng, B. Li, X. Duan, Mater. Today 2022, 57, 66.

[0017]

[12] L. Meng, Z. Zhou, M. Xu, S. Yang, K. Si, L. Liu, X. Wang, H. Jiang, B. Li, P. Qin, P. Zhang, J. Wang, Z. Liu, P. Tang, Y. Ye, W. Zhou, L. Bao, H.-J. Gao, Y. Gong, Nat. Commun. 2021, 12, 809.

[0018]

[13] C.Tan,J.Lee,SGJung,T.Park,S.Albarakati,J.Partridge,MRField,DGMcCulloch,L.Wang,C.Lee,Nat.Commun.2018,9,1554,1554.

[0019]

[14] G. Zhang, F. Guo, H. Wu, X. Wen, L. Yang, W. Jin, W. Zhang, H. Chang, Nat. Commun. 2022, 13, 5067.

[0020]

[15] B. Tang, X. Wang, M. Han, X. Xu, Z. Zhang, C. Zhu, X. Cao, Y. Yang, Q. Fu, J. Yang, X. Li, W. Gao, J. Zhou, J. Lin, Z. Liu, Nat. Electron. 2022, 5, 224.

[0021]

[16] Z.Fei,B.Huang,P.Malinowski,W.Wang,T.Song,J.Sanchez,W.Yao,D.Xiao,X.Zhu,AFMay,W.Wu,DHCobden,J.-H.Chu,X.Xu,Nat.Mater.2018,17,778.

[0022]

[17] W. Zhu, Y. Zhu, T. Zhou, X. Zhang, H. Lin, Q. Cui, F. Yan, Z. Wang, Y. Deng, H. Yang, L. Zhao, I. KDBelashchenko,K.Wang,Nat.Commun.2023,14,5371.

[0023]

[18] WKZhu,HLLin,FGYan,C.Hu,ZAWang,LXZhao,YCDeng,ZRKudrynskyi,T.Zhou,ZDKovalyuk,YHZheng,A.Patanè,I.Zutic,SSLi,HZZheng,KYWang,Adv.Mater.2021,33,2104658,2104658.

[0024]

[19] Z.Wang,D.Sapkota,T.Taniguchi,K.Watanabe,D.Mandrus,AFMorpurgo,Nano Lett.2018,18,4303. Summary of the invention

[0025] In view of the deficiencies of the prior art, an object of the present invention is to provide a magnetic tunnel junction; a second object of the present invention is to provide a method for preparing a magnetic tunnel junction.

[0026] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0027] A magnetic tunnel junction comprises a Cr3Te4 layer, a WS2 layer and a Fe3GeTe2 layer stacked in sequence, wherein the thickness of the WS2 layer is ≤4.2nm.

[0028] In the magnetic tunneling junction of the present invention, the thickness of the WS2 layer is ≤4.2nm, and its tunneling characteristics satisfy the linear tunneling mode, that is, the tunneling current and the applied voltage show a linear relationship. Under different current working conditions, the spin injection efficiency of the device is fixed, so that the resistance values ​​of the high resistance state and the low resistance state are the same under different current working conditions.

[0029] Furthermore, the thickness of the WS2 layer is 1.4-2.8 nm.

[0030] Furthermore, the thickness of the Cr3Te4 layer is ≤50nm, preferably 5-45nm, more preferably 10-40nm, and even more preferably 15-35nm; the thickness of the Fe3GeTe2 layer is ≤50nm, preferably 5-45nm, more preferably 10-40nm, and even more preferably 15-35nm.

[0031] Furthermore, the magnetization directions of the Cr3Te4 layer and the Fe3GeTe2 layer are the same or opposite.

[0032] Furthermore, the Cr3Te4 layer and the WS2 layer are bonded to each other through van der Waals force, and the WS2 layer and the Fe3GeTe2 layer are bonded to each other through van der Waals force, and no chemical bonds are formed between the layers.

[0033] Optionally, the Fe3GeTe2 layer has an out-of-plane easy magnetization axis.

[0034] Optionally, the Cr3Te4 layer has an out-of-plane easy magnetization axis.

[0035] In order to solve the problem that the residual glue left in the transfer process of the two-dimensional magnetic nanosheets causes the assembled out-of-plane magnetic tunnel junction to have a large resistance, the present invention first grows a two-dimensional Cr3Te4 / WS2 van der Waals heterojunction, and then prepares an out-of-plane magnetic tunnel junction with a structure of Cr3Te4 / WS2 / Fe3GeTe2 by dry transfer, so that an out-of-plane magnetic tunnel junction with a small working resistance can be obtained. The more specific method is as follows:

[0036] The method for preparing the magnetic tunnel junction as described above comprises the following steps:

[0037] S1, preparing a WS2 layer on a substrate by physical vapor deposition;

[0038] S2, growing a Cr3Te4 layer on the WS2 layer to obtain a substrate with a Cr3Te4 / WS2 heterojunction (two-dimensional);

[0039] S3. Transfer the Cr3Te4 / WS2 heterojunction to the Fe3GeTe2 layer by dry transfer to obtain a magnetic tunneling junction.

[0040] Therefore, the present invention can control the organic residues in the transfer process and reasonably control the thickness of the intermediate layer (WS2 layer), making it easier to prepare a magnetic tunnel junction with a lower working resistance, thereby promoting the development of low work function magnetic memory related technologies.

[0041] Further, in S1, in a tube furnace, the WS2 source is heated to 1100-1300°C, argon gas with a flow rate of 50-70 sccm is introduced, a substrate is placed 10-15 cm downstream of the WS2 source, and deposition is performed for 2-20 minutes to obtain a WS2 layer on the substrate; preferably, the substrate is a silicon wafer. Thus, a good preparation of the WS2 layer can be achieved, and the thickness of the WS2 layer can be controlled by controlling parameters such as deposition time and / or argon gas flow rate.

[0042] Further, in S2, in a tube furnace, a substrate with a WS2 layer is placed directly above a CrCl3 source, Te powder is placed on the upstream side of the CrCl3 source, the temperature of the CrCl3 source is controlled to be 540-650°C, the temperature of the Te powder is controlled to be 510-550°C, a mixed gas of argon and hydrogen is introduced, the flow rate of argon is 20-60sccm, the flow rate of hydrogen is 30-150sccm, and the growth is performed for 2-10min to obtain a Cr3Te4 / WS2 heterojunction;

[0043] Among them, the WS2 layer on the substrate faces the CrCl3 source;

[0044] Preferably, a CrCl3 source is placed in a loading boat with an open top, and the substrate with the WS2 layer is fixed on the loading boat just above the CrCl3 source, with the WS2 layer on the substrate facing the CrCl3 source. In this way, good growth of the Cr3Te4 layer can be achieved, and the operation can be completed using a general tube furnace, which is simple and efficient.

[0045] Further, in S3, when performing dry transfer, the substrate with the Cr3Te4 / WS2 heterojunction is first fumigated with hexamethyldisilazane vapor, and then a PMMA solution is coated on the side of the substrate with the Cr3Te4 / WS2 heterojunction, and after drying, a PMMA layer is obtained on the side of the substrate with the Cr3Te4 / WS2 heterojunction; then, after soaking in hot water at 80-100°C and cold water at 0-10°C respectively, the PMMA layer together with the Cr3Te4 / WS2 heterojunction is separated from the substrate by using a thermal release adhesive; and then, the WS2 layer of the Cr3Te4 / WS2 heterojunction on the PMMA layer is aligned and combined with the Fe3GeTe2 layer under a microscope to obtain a magnetic tunnel junction;

[0046] The solvent of the PMMA solution is an organic solvent, the concentration of PMMA is 1-12 wt %, preferably, the organic solvent is anisole. Optionally, the weight average molecular weight of PMMA is 480,000-520,000.

[0047] Furthermore, the fumigation time is 6-10 minutes; the drying treatment is carried out at 110-130°C for 1-3 minutes; and the soaking treatment is carried out in hot water at 80-100°C and cold water at 0-10°C for 3-10 minutes respectively.

[0048] The IV output curve of the magnetic tunnel junction of the present invention presents a straight line under the voltage of 0-1V, and the magnetic tunnel junction has a small resistance area (RA) <400kΩ·μm when working. 2 Therefore, the magnetic tunnel junction per unit area has a smaller resistance when working and consumes less power when conducting.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The magnetic tunnel junction of the present invention has a lower working resistance and can better meet the application requirements in low work function magnetic memory.

[0051] (2) The present invention can more accurately control the thickness of the WS2 layer, thereby achieving precise control of the tunneling resistance of the magnetic tunneling junction.

[0052] (3) The preparation process of the present invention does not require complicated operation steps or the use of expensive raw materials, and the equipment is simple, and the operation is simple and easy with good reproducibility.

[0053] (4) The magnetic tunnel junction of the present invention can achieve control of the resistance of the magnetic tunnel junction by regulating the magnetization direction of ferromagnetic Cr3Te4 and Fe3GeTe2. When the magnetization directions of Cr3Te4 and Fe3GeTe2 are the same, the magnetic tunnel junction exhibits low resistance; when the magnetization directions of Cr3Te4 and Fe3GeTe2 are opposite, the magnetic tunnel junction exhibits high resistance. By controlling the magnetization directions of Cr3Te4 and Fe3GeTe2, it is possible to convert information into a resistance signal and store it in the magnetic tunnel junction, so it is expected to be used in the data electronic information industry for data storage. In addition, when the magnetic structure of Cr3Te4 or Fe3GeTe2 is combined with other heavy metals, semi-metals or topological materials, the magnetic structure of Cr3Te4 or Fe3GeTe2 can be controlled by current and applied to magnetic random access memory. At the same time, according to the additional current design, it can also have certain logical operation functions, so as to be applied to the operator. Therefore, the magnetic tunnel junction of the present invention has good application value.

[0054] (5) The Cr3Te4 layer and Fe3GeTe2 layer on the surface of the WS2 layer of the present invention are both two-dimensional single crystal materials, and the easy magnetization directions of the two ferromagnetic layers are both out-of-plane, so there are no requirements for the shape and size of this magnetic tunnel junction, and it can be used in high-density storage devices. At the same time, since the materials of the ferromagnetic layers are different, the coercive force difference caused by the ferromagnetic layer materials is much larger than the coercive force difference caused by the same material thickness, so the off-state window of the magnetic tunnel junction of this structure is relatively large. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1a 3 is the IV curve of the magnetic tunnel junction of Example 1 of the present invention.

[0056] Figure 1b 3 is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction at 5 μA with the magnetic field according to Example 1 of the present invention.

[0057] Figure 1c 1 is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction at different currents as a function of magnetic field in Example 1 of the present invention.

[0058] Figure 2a It is the IV curve of the magnetic tunnel junction of Example 2 of the present invention.

[0059] Figure 2b 3 is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction at 5 μA with the magnetic field according to Example 2 of the present invention.

[0060] Figure 2c 1 is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction under different currents as a function of magnetic field according to Example 2 of the present invention.

[0061] Figure 3a It is the IV curve of the magnetic tunnel junction of Example 3 of the present invention.

[0062] Figure 3b 3 is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction at 5 μA as a function of magnetic field in Example 4 of the present invention.

[0063] Figure 3c 3 is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction under different currents as a function of magnetic field in Example 3 of the present invention.

[0064] Figure 4 It is a physical picture of the dual temperature zone tubular furnace of Example 1 of the present invention.

[0065] Figure 5 It is a schematic diagram of the loading boat and substrate assembly state of Example 1 of the present invention.

[0066] Figure 6a It is a cross-sectional high-angle annular dark-field scanning transmission electron microscope image and element distribution of the Cr3Te4 / WS2 / Fe3GeTe2 magnetic tunnel junction of Example 1 of the present invention.

[0067] Figure 6b This is the cross-sectional element distribution mapping of the Cr3Te4 / WS2 / Fe3GeTe2 magnetic tunnel junction of Example 1 of the present invention.

[0068] Figure 7a is the IV curve of the magnetic tunnel junction of Comparative Example 1 of the present invention.

[0069] Figure 7bThis is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction at 5 μA with the magnetic field in Comparative Example 1 of the present invention.

[0070] Figure 7c This is a curve showing the change of magnetic tunnel resistance of the magnetic tunnel junction at different currents with the magnetic field in Comparative Example 1 of the present invention.

[0071] Figure 8 It is an optical physical picture comparing the PMMA picking conditions in Example 1 (fumigation HMDS) of the present invention and Comparative Example 2 (fumigation HMDS). DETAILED DESCRIPTION

[0072] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0073] Example 1

[0074] The magnetic tunnel junction of this embodiment includes a Cr3Te4 layer, a WS2 layer and a Fe3GeTe2 layer stacked in sequence, wherein the thickness of the WS2 layer is 1.4 nm (double-layer WS2). The thickness of the Cr3Te4 layer is 27 nm; the thickness of the Fe3GeTe2 layer is 22 nm. The Cr3Te4 layer and the WS2 layer are bonded by van der Waals force, and the WS2 layer and the Fe3GeTe2 layer are bonded by van der Waals force. The Fe3GeTe2 layer has an out-of-plane easy magnetization axis.

[0075] The method for preparing the magnetic tunnel junction as described above is characterized by comprising the following steps:

[0076] S1, preparing a WS2 layer on a substrate by physical vapor deposition;

[0077] S2, growing a Cr3Te4 layer on the WS2 layer to obtain a substrate with a Cr3Te4 / WS2 heterojunction;

[0078] S3. Transfer the Cr3Te4 / WS2 heterojunction to the Fe3GeTe2 layer by dry transfer to obtain a magnetic tunneling junction.

[0079] In S1, in a tube furnace, the WS2 source is heated to 1200° C., argon gas with a flow rate of 60 sccm is introduced, and a substrate is placed 12 cm downstream of the WS2 source. Deposition is performed for 3 minutes to obtain a double-layer WS2 layer on the substrate; the substrate is a silicon wafer.

[0080] In S2, see Figure 4 In a dual-temperature zone tube furnace, the substrate with the WS2 layer was placed 0.5 cm above the CrCl3 source (located at Figure 4 In the middle right temperature zone), Te powder was placed 22 cm upstream of the CrCl3 source (located at Figure 4 In the middle left temperature zone), the temperature of the CrCl3 source is controlled at 625°C, the temperature of the Te powder is controlled at 515°C, a mixed gas of argon and hydrogen is introduced, the flow rate of argon is 40 sccm, the flow rate of hydrogen is 150 sccm, and the growth is carried out for 2 minutes to obtain a Cr3Te4 / WS2 heterojunction;

[0081] Among them, the WS2 layer on the substrate faces the CrCl3 source;

[0082] Place a CrCl3 source in a small boat (made of corundum) with an open top, and fix the substrate with the WS2 layer just above the CrCl3 source on the boat (see Figure 5 ) and make the WS2 layer on the substrate face the CrCl3 source.

[0083] In S3, when performing dry transfer, the substrate with the Cr3Te4 / WS2 heterojunction is first fumigated with hexamethyldisilazane vapor (HMDS) at 80°C for 8 minutes, and then PMMA (polymethyl methacrylate, [CH2C(CH3)(CO2CH3)] is coated on one side of the substrate with the Cr3Te4 / WS2 heterojunction. n , weight average molecular weight 495,000; manufacturer: KAYAKU; model: 495PMMA A8) solution, after drying at 120°C for 2 minutes, a PMMA layer is obtained on the side of the substrate having the Cr3Te4 / WS2 heterojunction; then, the substrate is immersed in hot water at 100°C and cold water at 0°C for 7 minutes respectively, and then a thermal release adhesive [PDMS (polydimethylsiloxane, (C2H6OSi) n )] The PMMA layer together with the Cr3Te4 / WS2 heterojunction was separated from the substrate (see Figure 8 ); then align the WS2 layer of the Cr3Te4 / WS2 heterojunction on the PMMA layer with the Fe3GeTe2 layer under a microscope, and after the combination is completed, the PMMA layer can be removed by soaking in acetone solution to obtain a Cr3Te4 / WS2 / Fe3GeTe2 magnetic tunnel junction on a silicon wafer substrate;

[0084] Wherein, the solvent of the PMMA solution is anisole, and the concentration of PMMA is 8wt%.

[0085] The Fe3GeTe2 layer is located on another substrate (silicon wafer), and the Fe3GeTe2 layer is prepared on the substrate by a lift-off method;

[0086] The microscope can be connected to a computer for real-time imaging, and the magnification can be adjusted within a range of 20 times to 400 times.

[0087] The on-state resistance of the magnetic tunnel junction at 50K is about 305Ω, which has a linear tunnel relationship. Its IV curve and magnetic tunnel resistance are shown in Figure 1. The overlapping area of ​​Cr3Te4 and Fe3GeTe2 in the tunnel junction is 50μm 2 , so the resistance area of ​​the tunnel junction is 0.305*50=15.25kΩ·μm 2 The off-state window of the magnetic tunnel junction is 750Oe. The resistance value does not change under different current conditions.

[0088] Example 2

[0089] Example 1 was repeated, with the only difference being that the thickness of the WS2 layer was 2.8 nm (four layers of WS2).

[0090] The on-state resistance of the magnetic tunnel junction at 50K is about 1305Ω, which has a linear tunnel relationship. Its IV curve and magnetic tunnel resistance are shown in Figure 2. The overlapping area of ​​Cr3Te4 and Fe3GeTe2 in the tunnel junction is 150μm 2 , so the resistance area of ​​the tunnel junction is 1.305*150=195.75kΩ·μm 2 The off-state window in this magnetic tunnel junction is 2100Oe.

[0091] Example 3

[0092] Example 1 was repeated, with the only difference being that the thickness of the WS2 layer was 4.2 nm (six layers of WS2).

[0093] The on-state resistance of the magnetic tunnel junction at 50K is about 2015Ω, which has a linear tunnel relationship. Its IV curve and magnetic tunnel resistance are shown in Figure 3. The overlapping area of ​​Cr3Te4 and Fe3GeTe2 in the tunnel junction is 190μm 2 , so the resistance area of ​​the tunnel junction is 2.015*190=382.85kΩ·μm 2 The off-state window in this magnetic tunnel junction is 2700Oe.

[0094] Comparative Example 1

[0095] Example 1 was repeated, with the only difference being that the thickness of the WS2 layer was 5.6 nm (eight layers of WS2).

[0096] The on-state resistance of the magnetic tunnel junction at 50K is about 22000Ω, which has a nonlinear tunnel relationship. Its IV curve and magnetic tunnel resistance are shown in Figure 7. The overlapping area of ​​Cr3Te4 and Fe3GeTe2 in the tunnel junction is 104μm 2 , so the resistance area of ​​the tunnel junction is 22*104=2288kΩ·μm 2The off-state window in the magnetic tunnel junction is 1450Oe. Under different current conditions, the resistance value changes.

[0097] Comparative Example 2

[0098] Example 1 was repeated, except that in S3, the fumigation treatment was omitted.

[0099] As a result, the PMMA layer together with the Cr3Te4 / WS2 heterojunction cannot be separated from the substrate normally (cannot be picked up by the thermal release adhesive, see Figure 8 ).

[0100] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A magnetic tunnel junction, characterized in that: It comprises a Cr3Te4 layer, a WS2 layer and a Fe3GeTe2 layer stacked in sequence, wherein the thickness of the WS2 layer is ≤4.2nm.

2. The magnetic tunnel junction according to claim 1, characterized in that: The thickness of the WS2 layer is 1.4-2.8 nm.

3. The magnetic tunnel junction according to claim 1, characterized in that: The thickness of the Cr3Te4 layer is ≤50nm, preferably 5-45nm, more preferably 10-40nm, and even more preferably 15-35nm; the thickness of the Fe3GeTe2 layer is ≤50nm, preferably 5-45nm, more preferably 10-40nm, and even more preferably 15-35nm.

4. The magnetic tunnel junction according to any one of claims 1 to 3, characterized in that: The magnetization directions of the Cr3Te4 layer and the Fe3GeTe2 layer are the same or opposite.

5. The magnetic tunnel junction according to any one of claims 1 to 3, characterized in that: The Cr3Te4 layer and the WS2 layer are bonded by van der Waals force, and the WS2 layer and the Fe3GeTe2 layer are bonded by van der Waals force.

6. The method for preparing a magnetic tunnel junction according to any one of claims 1 to 5, characterized in that: The steps include: S1, preparing a WS2 layer on a substrate by physical vapor deposition; S2, growing a Cr3Te4 layer on the WS2 layer to obtain a substrate with a Cr3Te4 / WS2 heterojunction; S3. Transfer the Cr3Te4 / WS2 heterojunction to the Fe3GeTe2 layer by dry transfer to obtain a magnetic tunneling junction.

7. The preparation method according to claim 6, characterized in that: In S1, in a tube furnace, a WS2 source is heated to 1100-1300° C., argon gas is introduced at a flow rate of 50-70 sccm, a substrate is placed 10-15 cm downstream of the WS2 source, and deposition is performed for 2-20 minutes to obtain a WS2 layer on the substrate; preferably, the substrate is a silicon wafer.

8. The preparation method according to claim 6, characterized in that: In S2, in a tube furnace, a substrate with a WS2 layer is placed directly above a CrCl3 source, Te powder is placed on the upstream side of the CrCl3 source, the temperature of the CrCl3 source is controlled to be 540-650°C, the temperature of the Te powder is controlled to be 510-550°C, a mixed gas of argon and hydrogen is introduced, the flow rate of argon is 20-60sccm, the flow rate of hydrogen is 30-150sccm, and the growth is carried out for 2-10min to obtain a Cr3Te4 / WS2 heterojunction; Among them, the WS2 layer on the substrate faces the CrCl3 source; Preferably, a CrCl 3 source is placed in a loading boat with an open top, and the substrate with the WS 2 layer is fixed directly above the CrCl 3 source on the loading boat, with the WS 2 layer on the substrate facing the CrCl 3 source.

9. The preparation method according to claim 6, characterized in that: In S3, when performing dry transfer, the substrate with the Cr3Te4 / WS2 heterojunction is first fumigated with hexamethyldisilazane vapor, and then a PMMA solution is coated on the side of the substrate with the Cr3Te4 / WS2 heterojunction. After drying, a PMMA layer is obtained on the side of the substrate with the Cr3Te4 / WS2 heterojunction; then, the substrate is soaked in hot water at 80-100°C and cold water at 0-10°C respectively, and then the PMMA layer is separated from the substrate together with the Cr3Te4 / WS2 heterojunction by using a thermal release adhesive; and then, the WS2 layer of the Cr3Te4 / WS2 heterojunction on the PMMA layer is aligned and combined with the Fe3GeTe2 layer under a microscope to obtain a magnetic tunnel junction; Wherein, the solvent of the PMMA solution is an organic solvent, the concentration of PMMA is 1-12 wt %, and preferably, the organic solvent is anisole.

10. The preparation method according to claim 9, characterized in that: The fumigation time is 6-10 minutes; the product is dried at 110-130℃ for 1-3 minutes; and the product is soaked in 80-100℃ hot water and 0-10℃ cold water for 3-10 minutes respectively.